CCIE collaboration quick reference - Behl, Akhil (Cisco Press, 2014)
CCIE Collaboration Quick Reference provides you with detailed information, highlighting the key topics on the latest CCIE Collaboration v1.0 exam. This fact-filled Quick Reference allows you to get all-important information at a glance, helping you to focus your study on areas of weakness and to enhance memory retention of important concepts. With this book as your guide, you will review and reinforce your knowledge of and experience with collaboration solutions integration and operation, configuration, and troubleshooting in complex networks. You will also review the challenges of video, mobility, and presence as the foundation for workplace collaboration solutions. Topics covered include Cisco collaboration infrastructure, telephony standards and protocols, Cisco Unified Communications Manager (CUCM), Cisco IOS UC applications and features, Quality of Service and Security in Cisco collaboration solutions, Cisco Unity Connection, Cisco Unified Contact Center Express, and Cisco Unified IM and Presence. This book provides a comprehensive final review for candidates taking the CCIE Collaboration v1.0 exam. It steps through exam objectives one-by-one, providing concise and accurate review for all topics. Using this book, exam candidates will be able to easily and effectively review test objectives without having to wade through numerous books and documents for relevant content for final review.